Demand for Freight Transport – Factors and Approaches for Research - Nikolova, Christina (Research Papers, 2021)
At the national level, there is no thorough and comprehensive study of freight demand and the factors that influencing it. This is actually the main objective of the study – to fill this gap in research on the subject and to define and analyse the various factors influencing freight demand by identifying a system of demand determinants that can be analysed regularly and which allows forecasting changes in freight volumes over certain periods of time.The research methods used in the research include elements of literature review, retrospective analysis, comparative and meaningful analysis and generalised ideas for systematising the main factors influencing the freight transport dеmand. The results of the survey are summaries and analyses that provide a basis for empirical research, analysis and forcasting of the demand for freight transport in the country.